1998
DOI: 10.1890/1051-0761(1998)008[0734:reonmi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Regional Estimation of Nitrogen Mineralization in Forest Ecosystems Using Geographic Information Systems

Abstract: A knowledge‐based geographic information system (GIS) model was developed and used to predict net nitrogen mineralization within forest ecosystems of the Midwestern Great Lakes region, USA (Illinois, Indiana, Michigan, Ohio, and Wisconsin). Climate, soil, and forest inventory data were used in conjunction with data relating initial N and lignin concentrations of leaf litter. Net N mineralization (Nnet) from leaf litter of forest ecosystems of the entire region was predicted as a function of litter quality (N:C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Increasing N mineralization rates correlating with increasing soil temperatures is consistent with the findings of several studies (e.g., Matson and Boone 1984;Powers 1990;Boone 1992;Kim et al 1995;Stottlemyer et al 1995;Sveinbjornsson et al 1995). The effect of temperature on community species composition and the resultant changes in litter quality and decomposition rates are routes whereby temperature can influence N mineralization rates (Matson and Boone 1984;Nadelhoffer et al 1991;Bale and Charley 1994;Fan et al 1998). In this study, substrate quality and N mineralization were correlated with each other, and with temperature, so the impact of temperature on N mineralization may be both direct and indirect.…”
Section: Influences On Net N Mineralizationsupporting
confidence: 90%
“…Increasing N mineralization rates correlating with increasing soil temperatures is consistent with the findings of several studies (e.g., Matson and Boone 1984;Powers 1990;Boone 1992;Kim et al 1995;Stottlemyer et al 1995;Sveinbjornsson et al 1995). The effect of temperature on community species composition and the resultant changes in litter quality and decomposition rates are routes whereby temperature can influence N mineralization rates (Matson and Boone 1984;Nadelhoffer et al 1991;Bale and Charley 1994;Fan et al 1998). In this study, substrate quality and N mineralization were correlated with each other, and with temperature, so the impact of temperature on N mineralization may be both direct and indirect.…”
Section: Influences On Net N Mineralizationsupporting
confidence: 90%
“…The response of N leaching and base cation mobility to N inputs at FEF (Adams et al 1997) suggests that cation availability eventually could limit forest productivity in the region, particularly in conjunction with harvesting (Gilliam and Adams 1999;Adams 1999). Although the rates of N mineralization reported for FEF are higher than those reported for most sites (Table 1, see also Pérez et al 1998), they are in agreement with modeled estimates of regional N mineralization rates by Fan et al (1998). Thus, conclusions for FEF may be applicable to otherwise similar, but unstudied, hardwood forests of the central Appalachian region of the eastern United States.…”
Section: Conclusion: Implications For Sustainable Forest Managementsupporting
confidence: 62%
“…Piao et al [15] suggested that new terrestrial biosphere models include nutrient limitations to account for the substantial effect of carbon-nitrogen interactions of climate variability and atmospheric CO 2 concentration on modeled carbon cycle. Fan et al [16] indicated that better predictions of forest ecosystem dynamics at the regional scale could be provided by using different nitrogen mineralization equations to relate to different regions and scales.…”
Section: Introductionmentioning
confidence: 99%
“…Many models have been developed to predict potential nitrogen mineralization measured via lab incubations [27,28]. However, few studies have scaled up field measurements and have estimated nitrogen mineralization at a regional scale [16,29]. Burke et al [30] utilized the CENTURY ecosystem model to estimate nitrogen mineralization for the US Central Plains region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation